Apologetics: A Justification For Contemporary Christian Beliefs - Mamosey, Tammy; Maramis, Fetrie JL (CV. Publikasi Indonesia, 2025)
The creation of this article is a collaboration between lecturers and students in carrying out the teaching and learning process at the Global Glow Indonesia College (STTGGI) Jakarta. Lecturers are in Jakarta, while students live in the USA. This article discusses the relevance and application of Christian apologetics in contemporary contexts, focusing on the presuppositional approach taken by John M. Frame. Apologetics, as a discipline that defends and justifies the Christian faith, is often confronted with modern intellectual and cultural challenges. Frame offers a unique framework, one that rejects autonomous neutrality and instead asserts the supremacy of divine revelation as the basis for all knowledge. The presuppositional approach argues that a person's basic assumptions, or